The removable acrylic partial denture in primary care: the experience and satisfaction of dental surgeons - Rita de Cássia SILVA; Raquel Conceição FERREIRA; Denise Vieira TRAVASSOS; Andréa Maria Duarte VARGAS (Universidade Estadual Paulista, 2017)
Abstract Introduction The guidelines of the National Politics of Oral Health have led to the inclusion of elemental prostheses in the list of Primary Care procedures. Objective This paper aimed to evaluate the performance and satisfaction of dental surgeons with the implementation of Acrylic Partial Dentures. Metodology The sample was composed by 159 dental surgeons (sample calculation), in Belo Horizonte, MG, Brazil, selected via raffle (simple random sampling). A structured questionnaire was built with 72 questions on the daily practice of the performance of dental surgeons, using the SurveyMonkey platform. Result The results showed that for most of dental surgeons, the inclusion on the list of primary care procedures was a positive initiative and they have enjoyed the experience of using Acrylic Partial Dentures. Dental surgeons who had graduated in private institutions reported to have had more failures than those who had graduated in public institutions. The better prepared dental surgeons reported less difficulties and failures, and the more satisfied professionals with the performance of Acrylic Partial Dentures related had also experienced fewer failures. Considering the indication, the majority of participants did it according to the protocol of the institution (only for anterior teeth) but many revealed the use of dentures also for premolars. Conclusion Acrylic partial dentures have been a reality in the Brazilian social context even before their inclusion in the list of Primary Care procedures. Such inclusion indicates their relevance; however, it is necessary to have their confection systematized by a protocol in public services.